Ox‐LDL induces endothelial cell apoptosis and macrophage migration by regulating caveolin‐1 phosphorylation. Issue 10 (9th May 2018) - Lin, Fei; Pei, Likai; Zhang, Qingbin; Han, Weizhong; Jiang, Shiliang; Lin, Yanliang; Dong, Bo; Cui, Lianqun; Li, Min
Abstract : Oxidative low‐density lipoprotein (ox‐LDL) is a risk factor for atherosclerosis. Ox‐LDL leads to endothelial injury in the initial stage of atherosclerosis. In this study, we investigated the role of ox‐LDL in endothelial injury and macrophage recruitment. We demonstrated that ox‐LDL promoted a dose‐dependent phosphorylation of caveolin‐1 in human umbilical vein endothelial cells. Phosphorylated caveolin‐1 increased ox‐LDL uptake. Intracellular accumulation of ox‐LDL induced NF‐κB p65 phosphorylation, promoted HMGB1 translocation from nucleus to cytoplasm and cytochrome C release from mitochondria to cytoplasm, and activated caspase 3, resulting in cell apoptosis. NF‐κB activation also facilitated cavolin‐1 phosphorylation and HMGB1 expression. In addition, caveolin‐1 phosphorylation favored HMGB1 release and nuclear translocation of EGR1. Nuclear translocation of EGR1 contributed to cytoplasmic translocation of HMGB1. The extracellular HMGB1 induced the migration of PMBC‐derived macrophages toward HUVECs in a TLR4‐dependent manner. Our results suggested that ox‐LDL promoted HUVECs apoptosis and macrophage recruitment by regulating caveolin‐1 phosphorylation. Abstract : Ox‐LDL‐induced phosphorylation of caveolin‐1 in human umbilical vein endothelial cells promoted ox‐LDL uptake, and in turn induced NF‐κB p65 phosphorylation, promoted HMGB1 translocation from nucleus to cytoplasm and cytochrome C release from mitochondria to cytoplasm, and activated caspase 3, resulting in cell apoptosis. Caveolin‐1 phosphorylation also favored HMGB1 release. The extracellular HMGB1 induced the migration of PMBC‐derived macrophages toward HUVECs.